Review: emulsion techniques for producing polymer based drug delivery systems - Nguyen, Thuy Chinh; Thai, Hoang (Vietnam Journal of Science and Technology, 2023)
Emulsification method is one of the popular methods for producing materials used in biosensing, bioimaging and others, especially, drug delivery polymer systems in microsize and nanosize. The concrete techniques related to this method are emulsification, self-emulsification, in a combination with solvent evaporation process, homogenization, or ultranosication. The structure of emulsion formulation consists of two phases: an internal phase and an external phase. Based on the structure and nature of the phases, emulsions can be classified into different types such as two-phase systems (oil in water emulsion (O/W) or water in oil emulsion (W/O)) or three-phase systems (water in oil in water triple emulsion (W/O/W) or oil in water in oil triple emulsion (O/W/O)). The droplet sizes in micro-emulsion systems are often higher than 1 m while those in nano-emulsions or mini-emulsions are in the range of 100-500 nm. Some special nano-emulsion systems can contain droplets with a size of few nanometers. Factors including solvents, oil/water phase ratio, droplet oil size, composition ratio, nature of raw materials, emulsifiers, etc. can affect the morphology, properties, and size of the obtained products. This paper reviews emulsion techniques which have been applied for producing polymeric drug delivery systems. The components, properties, characteristics, encapsulation efficiency as well as drug release rate, water solubility, toxicity and administration efficacy of drug emulsion formulations will be mentioned. Advantages and limitations of emulsion techniques are also discussed.